Petasites hybridus in migraine prophylaxis: literature review - Silva-Néto, Raimundo Pereira (Headache Medicine, 2024)
Introduction Over the past 25 years, Petasites hybridus has been used effectively in migraine prophylaxis. It acts on its pathophysiological mechanisms, modulating nociception, reducing the release of CGRP, decreasing inflammatory mediators and blocking calcium channels. Objective To review clinical studies already published on Petasites hybridus in migraine prophylaxis, with emphasis on the initial study by Grossmann and Schmidramsl in 2000. Methods This study was an integrative and retrospective review of articles on the use of Petasites hybridus in the prophylactic treatment of migraine that were published in English in the last 25 years. Results Five clinical studies were found, all placebo-controlled, three of which were double-blind, involving 488 patients with migraine aged between 6 and 60 years. These studies showed that Petasites hybridus was superior to placebo, proving its effectiveness in the prophylactic treatment of migraine and with good tolerability, including by children and adolescents. Conclusions Clinical studies proved that Petasites hybridus was well tolerated by children and adults and effective in migraine prophylaxis, reducing the number of days with headache by ≥ 50% in the first three months.